Preparation of Mini Granulator for Encapsulation of Plant Seed Based on Biochar Powder - Hery Nirwanto; Penta Suryaminarsih; Setyo Budi Santoso (Future Science, 2022)
The preparation of an engineered mini granulator is used as a way to encapsulate horticultural plant seeds for farmers in Gandusari village, Blitar, for the need for healthy seeds, especially during the rainy season. This experiment aims to determine the performance of the self-designed encapsulation device, using a DC motor drive. The construction of the mini granulator consists of a frame to support a stainless steel drum as a container for seeds and adhesives, measuring 50 cm in diameter and 40 cm in height, which is supported by a motor axis with a length of 5 cm with a distance of 15 cm from the iron frame. The drum is placed perpendicular to the motor axis vertically and is supported by an iron frame that is hinged at the edges so that the drum can be tilted while rotating. The tilt of the drum when rotating has an angle of 30 degrees, so that the seeds that have been mixed with adhesives and organic materials can form granules with the help of a sprayer filled with water to wet the mixed ingredients. The mini granulator test was carried out with carrier materials as a medium for microbial viability. The microbes used were from the fungal group in the form of Trichoderma isolates and from the bacterial group in the form of Streptomyces isolates. The manufacture of encapsulated seeds is done by placing the seeds and the adhesive mixture into the drum. The granulation method used is the wet granulation method. A total of 1 g of vegetable seeds were put into the encapsulation drum, then sprayed with adhesive solution 5 times (± 2 ml), then 1 g of dry material in the form of biochar was added. The speed of the granulator obtained was about 200 rpm, after 1 minute, the rotation was stopped, then the coated seeds were filtered in a 200 mesh (75 µm) sieve. Seed coating sessions were carried out 6 times, but in the 2nd session, the dry matter included was CaCO3. The seeds were then air-dried for 30 minutes, then put and stored in an aluminum foil pouch.